ChemInform Abstract: Boron and Nucleic Acid Chemistries: Merging the Best of Both Worlds. Issue 36 (15th August 2013) - Martin, Anthony R.; Vasseur, Jean‐Jacques; Smietana, Michael
Abstract Review: 222 refs.